Ultraviolet/persulfate (UV/PS) pretreatment of typical natural organic matter (NOM): Variation of characteristics and control of membrane fouling. (January 2019) - Wang, Zongping; Wan, Ying; Xie, Pengchao; Zhou, Aijiao; Ding, Jiaqi; Wang, Jingwen; Zhang, Li; Wang, Songlin; Zhang, Tian C.
Abstract: The effects of ultraviolet/persulfate (UV/PS) pretreatment on ultrafiltration (UF) membrane fouling caused by typical natural organic matter (NOM) fractions including humic acid (HA), sodium alginate (SA), and bovine serum albumin (BSA) were investigated. UF membrane fouling during the filtration of different NOM fractions after UV/PS pretreatment was compared through the evaluation of normalized membrane flux decline and membrane fouling reversibility. The fouling mitigation mechanisms were investigated through the characterization of ultraviolet absorbance (UV254 ), dissolved organic matter, zeta potential, particle size distribution, fluorescence excitation-emission matrix spectra, and fitness of four classic fouling models. Furthermore, the fouled membranes were characterized by Fourier-transform infrared spectroscopy and scanning electron microscopy. The results showed that UV/PS pretreatment significantly alleviated membrane fouling caused by HA, SA, and HA-SA-BSA mixture, and the fouling control performance improved at high PS doses. However, either UV alone or UV/PS pretreatment at low PS dose (10 mg/L) significantly aggravated BSA fouling with the normalized flux at the end of first filtration cycle being 8% and 15%, respectively. The increased particle size of BSA after UV/PS pretreatment was attributed to the formation of aggregates, which mainly accumulated in membrane pores and aggravated membrane fouling. Modeling results suggest that the mitigation of membrane fouling derived from SA and mixed organic fractions was primarily ascribed to the control of cake filtration, while the mitigation of HA fouling was attributed to the declined contribution of standard blocking. Graphical abstract: Image 1 Highlights: Effects of UV/PS pretreatment on membrane fouling derived from typical organic fractions were investigated. UV/PS significantly eased membrane fouling by HA, SA, and HA-SA-BSA mixture, rather than BSA. Either UV radiation or UV/PS at a low PS dose (10 mg/L) caused severe BSA-based membrane fouling. The particle size of HA, BSA, and HA-SA-BSA mixture increased after UV/PS pretreatment.